2003
DOI: 10.1308/003588403321219885
|View full text |Cite
|
Sign up to set email alerts
|

Referral guidelines for colorectal cancer – do they work?

Abstract: Aims and Methods: Urgent referral guidelines for patients with suspected colorectal cancer were introduced in 2000. In a district general hospital, we prospectively assessed the effect of these guidelines on the number of urgent referrals received and the number found to have cancer. Results: Over the first year, 180 urgent referrals were received of whom 95 (55%) fitted the guidelines. Of these 95 patients, 24 (25%) had colorectal cancer. Conversely, only 2 of the 85 patients (2%) who did not fit the guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 4 publications
(6 reference statements)
6
41
1
Order By: Relevance
“…Many studies have reported no significant difference in the stage of the disease in CRC patients referred via the TWR compared with other referral routes [12,14,19,26,31]. This finding was supported by a study by Kiran et al, who reported that there was no relation between the duration of CRC symptoms and the stage at presentation [55].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Many studies have reported no significant difference in the stage of the disease in CRC patients referred via the TWR compared with other referral routes [12,14,19,26,31]. This finding was supported by a study by Kiran et al, who reported that there was no relation between the duration of CRC symptoms and the stage at presentation [55].…”
Section: Discussionmentioning
confidence: 74%
“…Another explanation may be that emergency referrals would never see a GP to allow a TWR referral to be instigated. Those articles quoting the proportion of GI cancer patients diagnosed via the A&E route state numbers ranging from 13.4% -35.3% for CRCs [12,14,15,17,19,21,27,31,32] and from 31% -41% for UGCs [37,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The Department of Health introduced national referral guidelines for colorectal cancer in 2000. These were based on high-risk symptoms and were designed to identify patients with a high probability of cancer who should be seen by a hospital specialist within two weeks of referral by their general practitioner and are termed Btarget wait referralsô r Btwo-week wait referrals.^Iron deficiency anemia without an obvious cause is one such high-risk criterion for urgent referral to a colorectal specialist according to this Btwo-week rule.^9 , [12][13][14][15] However, from our study we found that patients with iron deficiency anemia were far more likely to be referred as nonurgent cases to a gastroenterologist probably because not all of them have lower gastrointestinal symptoms. This caused significant delays, with a mean of 60 days from referral to diagnosis compared with 31 days for those referred urgently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some patients identified practitioners as gatekeepers and a potential barrier to their referral since the patient waited for the GP to act on their behalf (Bain et al, 2002). Although limited, there is some evidence to suggest that appropriate referral and use of referral guidelines is associated with reduced delay (Holliday and Hardcastle, 1979;Debnath et al, 2002;Eccersley et al, 2003). Practitioners in rural areas were less likely to refer, due to the distance from specialist services (Sladden and Thomson, 1998) (Table 2).…”
Section: Practitioner Behaviourmentioning
confidence: 99%